Shoulder injuries in tennis players - van der Hoeven, H.; Kibler, W. B. (British Journal of Sports Medicine, 2006)
The mechanism of the overhead action in throwing sports has been studied extensively. This motion is unnatural and highly dynamic, often exceeding the physiological limits of the joint. Owing to overload of various anatomical structures, the shoulder is susceptible to injury. Optimal shoulder function requires good kinetic chain function, optimal stability, and coordination of the scapula in the overhead action. A well balanced action of the rotator cuff muscles and capsular structures is necessary to obtain a stable centre of rotation during the overhead action. This review concerns shoulder injuries, related to the overhead motion in tennis players, which can be explained by the same mechanism as thrower`s shoulder.